Pengaruh Profitabilitas, Ukuran Perusahaan dan Corporate Social Responsibility terhadap Tax Avoidance pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2018-2022 - Nova, Setevani; Untung, Untung; Zainudin, Zainudin (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study is a quantitative research that aims to find out how the effect of Profitability proxied with (NPM), Company Size proxied by (SIZE) and Corporate Social Responsibility proxied by (CSRli) on Tax Avoidance proxied with (ETR) in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the IDX for the 2018-2022 Period. The number of samples in this study is 115 companies with a sample withdrawal method using the purposive sampling method. The data used was sourced from secondary data, then the data collected was analyzed using descriptive analysis methods and multiple linear regression analysis followed by normality tests, multicollinearity tests, autocorrelation tests, and heteroscedasticity tests. Analysis of research data processing using SPSS Statistics 25. Based on the results of the study, it shows that simultaneously profitability, company size and corporate social responsibility have a significant effect on tax avoidance. And the test results partially show that profitability has no effect on tax avoidance, company size has a positive effect on tax avoidance and corporate social responsibility has a negative effect on tax avoidance.